Leadership Analysis at the Sharia Economics Forum, Faculty of Economics and Islamic Business - Putri, Bella Ivanka; Hidayattullah, Nur Wahid; Yeamari, Revaju; Pratiwi, Cindy Afifah Surya (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2024)
Human resource development is the main strategy undertaken by companies to increase production and productivity. Referring to leadership in an organization of the Sharia Economic Forum which is engaged in the field of Islamic economics. An organization needs leadership because it will make simpler to realize its goal since there will be people in charge of effectively coordinating human resources. The findings of study done through in-person interviews with sources who are the chairman or president of Raden Mas Said State Islamic University's Sharia Economic Forum. In order to write this article with qualitative descriptive methods through interviews, it is expected that with good leadership, the organization will develop well, without a good leader, the organization will certainly be destroyed even with adequate human resources. The results of the research show that leadership in the Sharia Economic Forum organization is very influential, especially regarding the development of Human Resources in the organization. It is hoped that this group may become even more widespread among Raden Mas Said State Islamic University students as well as students at other universities with improved leadership on a daily basis.